Hubungan Volatilitas dan Volume Perdagangan di Bursa Efek Indonesia - Bambang Sutrisno (Esensi: Jurnal Bisnis dan Manajemen, 2017)
The Relationship Between Volatility and Trading Volume in The Indonesian Stock ExchangeThere are a lot of studies that examine the relationship between volatility and trading volume in the stock exchange. This study is conducted to examine the role of trading frequency and volume in explaining the volatility-volume relationship in the Indonesia Stock Exchange (IDX). The analysis is conducted at the firm level with samples of 38 individual stocks from January 2012 to December 2013. The results show that there is a positive relationship between volatility and trading frequency as well as between volatility and trading volume. The results also find that trading frequency is better than trading volume in explaining volatility.DOI:  10.15408/ess.v7i1.3894